1997
DOI: 10.1136/vr.140.24.617
|View full text |Cite
|
Sign up to set email alerts
|

Influence of orchiectomy on canine behaviour

Abstract: One hundred and twenty-two dog owners were interviewed to obtain information about the effects of orchiectomy on the behaviour, unwanted side effects, and testosterone-dependent disease processes in their dogs. Behavioural problems were the main reason for orchiectomy, unwanted sexual behaviour being the most common, together with roaming, aggression, and abnormal urination behaviour. Objectionable sexual behaviour, inter-male aggression, roaming, and abnormalurination were reduced after orchiectomy in approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
1
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 11 publications
3
59
1
10
Order By: Relevance
“…Investigators of 1 study 110 reported decreased activity in 50% of male dogs neutered as adults, contrary to results of an earlier study 113 in which there was no indication that neutered male dogs become more inactive or lethargic. Additional differences were for dogs gonadectomized at 7 weeks or 7 months of age, which were judged to be more excitable than were sexually intact dogs.…”
Section: Orthopedic Diseasescontrasting
confidence: 53%
See 1 more Smart Citation
“…Investigators of 1 study 110 reported decreased activity in 50% of male dogs neutered as adults, contrary to results of an earlier study 113 in which there was no indication that neutered male dogs become more inactive or lethargic. Additional differences were for dogs gonadectomized at 7 weeks or 7 months of age, which were judged to be more excitable than were sexually intact dogs.…”
Section: Orthopedic Diseasescontrasting
confidence: 53%
“…2,15,28,29,110,[112][113][114] In males, the age at castration or duration of the behavior does not change the likelihood that surgery will alter these unwanted behaviors. 113,114 The literature provides consistent results regarding the effects of gonadectomy on behaviors driven by testosterone or estrogen; however, studies involving behaviors not directly related to gonadal steroid hormones have resulted in mixed findings.…”
Section: Orthopedic Diseasesmentioning
confidence: 99%
“…Behavior problems are one of the primary reasons for owners to request neutering of male dogs even if there is no support of an effect of neutering on behavior problems. Previous studies have showed that only sexually dimorphic behaviors like urine-marking, mounting and roaming are usually reduced by neutering (Maarschalkerweerd et al, 1997;Neilson et al, 1997). To neuter dogs with behavior problems that are not related to sexual behavior (like fearfulness or anxiety) would therefore not be expected to give a positive outcome.…”
Section: Discussionmentioning
confidence: 98%
“…O'Farrell and Peachey suggested spayed bitches showed higher aggression than females. However, aggression was increased if the bitch already showed signs of aggression making the causal link questionable, and there were differences in the control and experimental (desexed) group at first interview in factors such as prior treatment with synthetic progestogen, making confounding likely 52. In a cross-sectional survey of English Cocker Spaniels, links between neutering and increased aggression were found in both males and females, but when the analysis was restricted only to dogs desexed prior to aggression being displayed, a significant effect remained only in neutered females for aggression towards children in the household, but not for the other 12 types of aggression 54.…”
Section: Discussionmentioning
confidence: 99%